Implementation of a module for risk of ozone impacts assessment to vegetation in the Integrated Assessment Modelling system for the Iberian Peninsula. Evaluation for wheat and Holm oak. - de Andrés, Juan Manuel; Borge, Rafael; de la Paz, David; Lumbreras, Julio; Rodríguez, Encarnación (Environmental pollution (Barking, Essex : 1987), 2012)
A module to estimate risks of ozone damage to vegetation has been implemented in the Integrated Assessment Modelling system for the Iberian Peninsula. It was applied to compute three different indexes for wheat and Holm oak; daylight AOT40 (cumulative ozone concentration over 40 ppb), cumulative ozone exposure index according to the Directive 2008/50/EC (AOT40-D) and POD(Y) (Phytotoxic Ozone Dose over a given threshold of Y nmol m(-2) s(-1)). The use of these indexes led to remarkable differences in spatial patterns of relative ozone risks on vegetation. Ozone critical levels were exceeded in most of the modelling domain and soil moisture content was found to have a significant impact on the results. According to the outputs of the model, daylight AOT40 constitutes a more conservative index than the AOT40-D. Additionally, flux-based estimations indicate high risk areas in Portugal for both wheat and Holm oak that are not identified by AOT-based methods.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 22398018
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: toxicity; Chemical; CMAQ WRF; Critical level; Environmental Monitoring; Environmental Monitoring: methods; iberian peninsula; Models; Ozone; Ozone risk assessment; Ozone: analysis; Ozone: toxicity; Portugal; Quercus; Quercus: drug effects; Quercus: growth & development; Risk Assessment; Stomatal conductance; Triticum; Triticum: drug effects; Triticum: growth & development

Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest

The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment